IEEE PES Innovative Smart Grid Technologies, Europe 2014
DOI: 10.1109/isgteurope.2014.7028951
|View full text |Cite
|
Sign up to set email alerts
|

A new reward-penalty mechanism for distribution companies based on concept of competition

Abstract: In this paper, a new method for designing procedure of Reward-Penalty Scheme (RPS) in distribution system is proposed. Being fair and adoptable in viewpoint of distribution companies (DisCos) are main superiorities of the proposed RPS. Established based on concept of the Yardstick theory, its application can ensure regulators that a perfect competition will be created between DisCos to improve the service reliability. Also, such a regulation scheme can be a key for power system decision makers in order to prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The third condition guarantees practicality of the proposed algorithm and decreases computational burden of the studies. To apply this condition, it has been shown that correlation indices can be used to properly determine the degree of similarity of various features . The fourth condition is required because the ultimate objective of this stage is to compare the reliability indices of similar companies.…”
Section: Similar Companies Clusteringmentioning
confidence: 99%
“…The third condition guarantees practicality of the proposed algorithm and decreases computational burden of the studies. To apply this condition, it has been shown that correlation indices can be used to properly determine the degree of similarity of various features . The fourth condition is required because the ultimate objective of this stage is to compare the reliability indices of similar companies.…”
Section: Similar Companies Clusteringmentioning
confidence: 99%
“…Nevertheless, this approach does not necessarily guarantee an equal reliability level for similar customers, which are located in different areas but are subject to identical external conditions 16‐18 . Traditional reliability incentive regulations identically treat different customers located in different geographic areas and even in the territory of diverse DISCOs 19,20 . Although different unreliability costs for similar customers, for example, commercial, industrial, and residential, in different locations, might be justified based on their unequal opportunities, four problems are seen.…”
Section: Introductionmentioning
confidence: 99%
“…Since these frameworks were outlined and kept up to exclusive expectations, this disintegration was not apparent immediately. The reliability quality appeared to be satisfactory for quite a long time, yet it then began to break down quickly (Jooshaki 2014;Brown and Burke 2000). At the point of unwavering reliability, issues pertaining to quality became apparent as organizations do not regularly have the required assets to resolve the issue (Wangdee 2005), .…”
Section: Introductionmentioning
confidence: 99%